Autophagy and Cancer Dormancy - Akkoc, Yunus; Peker, Nesibe; Akcay, Arzu; Gozuacik, Devrim (Frontiers in Oncology, 2021)
Metastasis and relapse accounts for the great majority of cancer-related deaths. Most metastatic lesions are micro metastases that have the capacity to remain in a non-dividing state called “dormancy” for months or even years. Commonly used anticancer drugs generally target actively dividing cancer cells. Therefore, cancer cells that remain in a dormant state evade conventional therapies and contribute to cancer recurrence. Cellular and molecular mechanisms of cancer dormancy are not fully understood. Recent studies indicate that a major cellular stress response mechanism, autophagy, plays an important role in the adaptation, survival and reactivation of dormant cells. In this review article, we will summarize accumulating knowledge about cellular and molecular mechanisms of cancer dormancy, and discuss the role and importance of autophagy in this context.